Gestão de riscos: um estudo multicasos do processo de contratação de mão de obra terceirizada na Universidade Federal de Santa Maria - Pilger, Alex Haubert (2024)
This study aimed to evaluate the risks existing in outsourced labor contracts, and from this to propose a risk management tool aimed at minimizing the risks existing in the process of hiring outsourced labor at the Federal University of Santa Maria. With the growing need to comply with current legislation and the considerable number of outsourced employees in the institution, the management of administrative contracts faces challenges related to exposure to various risks, the failure to manage which can result in losses to public administration. In this context, the research sought to investigate the feasibility of a risk management tool that could serve as a model or methodological proposal in the processes of hiring outsourced labor by UFSM, assisting in decision-making in uncertain contract environments. The methodology adopted is exploratory and qualitative in nature, configuring itself as a multi-case study based on four outsourced service contracts at UFSM. Four contract managers or sector inspectors were interviewed and data analysis was carried out using the content analysis technique, allowing a more in-depth understanding of the interviewees' responses and the identification of relevant patterns and themes. The results revealed the lack of application of the formal risk management policy, gaps in knowledge on the topic on the part of some interviewees and the lack of risk mapping in contracts. This research contributed to a more in-depth understanding of the challenges faced in the management of outsourced labor contracts at UFSM and suggests the need to implement risk management measures to mitigate potential adverse impacts. However, the fact that it was carried out in a single institution is considered a limitation. This limits the generalization of the results to other universities or institutions of different sizes, sectors or contexts.